2021
DOI: 10.17356/ieejsp.v7i3.786
|View full text |Cite
|
Sign up to set email alerts
|

Gaining trust and remaining mentally sane while working from home : The importance of employee wellbeing

Abstract: The COVID-19 pandemic has hit us hard. It is not only difficult in terms of psychological and medical issues, but it has turned into an economic crisis as well. One of the most significant ‘side effects’ of the first wave was widespread remote work, which was not regular – many people had to work from home while also taking care of their loved ones (be they children or other family members, or friends). Our research – part of an EU-funded project on sustainable mobility – was carried out in the city of Szeged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…About half of Chinese healthcare workers have reported high levels of depression and anxiety since the outbreak of COVID-19 [ 4 ]. Moreover, Hungarian workers reported increased stress and mental fatigue, derived from new work arrangements including working from home [ 5 ]. Literature reviews have identified that working from home can be a stressor for some employees, associated with stress, depression and fatigue [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…About half of Chinese healthcare workers have reported high levels of depression and anxiety since the outbreak of COVID-19 [ 4 ]. Moreover, Hungarian workers reported increased stress and mental fatigue, derived from new work arrangements including working from home [ 5 ]. Literature reviews have identified that working from home can be a stressor for some employees, associated with stress, depression and fatigue [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%